Sinergi Stakeholder Dalam Mewujudkan Aktivitas Pariwisata Di Desa Wisata Baha, Kecamatan Mengwi, Kabupaten Badung - Haryanti, Lena; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2018)
The purpose of this research is to know the existence of stakeholder in tourism in the tourist village of Baha, as well as synergies between tourism stakeholder in the Baha tourism village in making Baha as a tourism village in Badung Regency This research is located in Baha village, Mengwi Subdistrict, Badung Regency. The type of research is in the form of qualitative data and quantitative data. The data sources obtained from the primary data and secondary data. The method of data collecting used are observation, interviews, and literature study. The determination of informants used purposive sampling. Data analysis technique used descriptive qualitative. The results of this study revealed that the presence of stakeholder in tourism in the tourist village of Baha, that consists of: (1) Government (Tourism Office of Badung Regency and the Dinas village of Baha). (2) The organizers of tourism business, comes from the local community who made their houses as homestays, and (3) local communities play a role in tourist attraction, which is coordinated by POKDARWIS. Based on the synergy between stakeholder involved in Baha tourism, can be said that the synergies between tourism stakeholder in Baha tourism village has not been maximum yet.   Keywords : Synergies,Stakeholder,Baha Tourism Village